The American stud book : containing full pedigrees of all the imported thorough-bred stallions and mares, with their produce
"Including the Arabs, Barbs and Spanish horses, from the earliest accounts of racing in America, to the end of the year ... ; also all the native mares, and their produce, alphabetically arranged, with an appendix, giving pedigrees of all the native stallions whose dams have no names, with full and copious index to produce of the mares."